Relação família e escola na educação infantil: a reunião de pais em foco - Zoadelli, Cristiane Lino (2018)
This intervention-research seeks to answer the following questions: How does the pre-school teacher conduct parent-teacher conference? What are the perceptions about parent-teacher conferences conducted by the pre-school teacher and possible ways to address them? What do mothers say about and propose for the conferences? Its main objective is to analyze how the parent-teacher conference is conducted in a kindergarten school. As specific objectives we highlight the following: observe how pre-school teachers conduct parent-teacher conferences; discuss with teachers our insights about parent-teacher conference conducted by the pre-school teacher and possible ways to address them; verify and analyze the participation of families and what mothers say about and propose for the conference. The hypothesis is that pre-school teachers, despite knowing the importance of family in the school, most of them conduct parent-teacher conference in an authoritarian, unilateral manner and do not make room for dialogue with families and their contributions. The research universe is a municipal public school for children's education, located in the city of São Bernardo do Campo, metropolitan region of the state of São Paulo. The subjects are a teacher, who teaches in kindergarten with children from 3 to 4 years of age and two mothers. The methodology used is qualitative of the intervention type based on action research from the action-reflection-action perspective proposed by Paulo Freire and the instruments of data collection are observation of the conferences conducted by the teacher, semi-structured interviews with the mothers and subsequent dialogue between that teacher and those mothers. To support childhood education category, we use the following authors: Kramer, Oliveira; to support the category family and school, we refer to Szymanski, Freire. Finally, to base the category of parenting we use the ideas of Althuon, Essle, Stoeber and Galluzzi. It is concluded that the parent-teacher conferences in the nursery school can be moments of exchange between school and families. All the mothers, through interviews, revealed how important was the active participation and contribution of family, both in the improvement of the parents' conference and in the pedagogical work done with children. One of the mothers suggested that the name of the parent-teacher conference should be changed to family conferences, since there are other children’s caregivers, such as grandparents and older siblings. We found it to be indispensable, the fact that teachers have been looking forward to the changes, the innovation and making room for effective dialogue between schools and families can happen democratically.